KEMAMPUAN ISTILAH ILMIAH MAHASISWA PENDIDIKAN GURU SEKOLAH DASAR AKADEMI KEGURUAN PARIS BARANTAI KOTABARU (Studi Kasus pada Mahasiswa Pengikut Mata Kuliah Pendidikan Bahasa dan Sastra Indonesia di Kelas Tinggi) - Sofyan Hamid (CENDEKIA: JURNAL ILMIAH PENDIDIKAN, 2010)
Mastering the vocabulary of scientific terms for someone is one aspect that makes it easy to interact/communicate in both official and unofficial meeting. Ascertained style and character of a person in speech especially in front of a multidimensional audies provides its own assessment of the impression conveyed language. This study aims to identify the ability of students of primary School Teacher training of respod introductory language courses if lecturers use scientific terms either orally or in writing in terms of critical response and the results obtained.The subject of this research is primary School Training of AKPB Kotabaru year 2006, is which they follow Indonesian language and literature at Height Class lectures. It was conducted at 3rd semester. The subjects were divided into two classes based on the homogeneity of subjects obtained. Classes of the semester 1 and 2 are given the introductory of language integrated use of scientific terms (class A) and the other class is given an introduction of simple language in case of involving the Indonesian language and region with record syllabus, material / lecture material, to test questions equal distribution (class B).Test results are analyzed based on the velocity value obtained by completing the test of time each student by using descriptive statistics: the size of centralization of symptoms (mean, median and mode), the size distribution of symptoms (range, standard deviation, quartile 1 and quartile 3).The result showed that the ability of students AKPB Kotabaru understanding of scientific terms if given test problem with the language of instruction components that implement the terms and scientific vocabulary in terms of space time and the results obtained is still low when compared with the test questions provided by a language of instruction which collaborates with a variety or dialect of everyday. Kata-kata kunci: Kemampuan, mahasiswa, istilah/kosakata ilmiah, dan berkomunikasi